β‐catenin signaling modulates the tempo of dendritic growth of adult‐born hippocampal neurons - Heppt, Jana (EMBO J, 2020)
In adult hippocampal neurogenesis, stem/progenitor cells generate dentate granule neurons that contribute to hippocampal plasticity. The establishment of a morphologically defined dendritic arbor is central to the functional integration of adult‐born neurons. We investigated the role of canonical Wnt/β‐catenin signaling in dendritogenesis of adult‐born neurons. We show that canonical Wnt signaling follows a biphasic pattern, with high activity in stem/progenitor cells, attenuation in immature neurons, and reactivation during maturation, and demonstrate that this activity pattern is required for proper dendrite development. Increasing β‐catenin signaling in maturing neurons of young adult mice transiently accelerated dendritic growth, but eventually produced dendritic defects and excessive spine numbers. In middle‐aged mice, in which protracted dendrite and spine development were paralleled by lower canonical Wnt signaling activity, enhancement of β‐catenin signaling restored dendritic growth and spine formation to levels observed in young adult animals. Our data indicate that precise timing and strength of β‐catenin signaling are essential for the correct functional integration of adult‐born neurons and suggest Wnt/β‐catenin signaling as a pathway to ameliorate deficits in adult neurogenesis during aging.